1997
DOI: 10.1163/156853097x00132
|View full text |Cite
|
Sign up to set email alerts
|

The Abuse of Animals and Domestic Violence: A National Survey of Shelters for Women who are Battered

Abstract: The maltreatment of animals, usually companion animals, may occur in homes where there is domestic violence, yet we have limited information about the prevalence of such maltreatment. We surveyed the largest shelters for women who are battered in 49 states and the District of Columbia. Shelters were selected if they provided overnight facilities and programs or services for children. Ninety-six percent of the shelters responded. Analysis revealed that it is common for shelters to serve women and children who t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(20 citation statements)
references
References 11 publications
0
18
0
2
Order By: Relevance
“…Abusing animals is another effective tactic used by perpetrators to instill fear, prevent victims from leaving, manipulate children within the home, and provide a preliminary precursor to suggest the violence the perpetrator intends to inflict on the victim(s) (Gallagher et al, 2008). An association between animal abuse with domestic violence as well as child abuse is supported by literature; its presence could be an indication of the escalation of violence toward others within the home (Ascione et al, 1997;Becker & French, 2004). Arkow (1992) reported that cruelty to animals is "symptomatic of disturbed individuals and dysfunctional families, and a predictor of human violence" (p. 521).…”
Section: Human and Animal Violencementioning
confidence: 98%
See 2 more Smart Citations
“…Abusing animals is another effective tactic used by perpetrators to instill fear, prevent victims from leaving, manipulate children within the home, and provide a preliminary precursor to suggest the violence the perpetrator intends to inflict on the victim(s) (Gallagher et al, 2008). An association between animal abuse with domestic violence as well as child abuse is supported by literature; its presence could be an indication of the escalation of violence toward others within the home (Ascione et al, 1997;Becker & French, 2004). Arkow (1992) reported that cruelty to animals is "symptomatic of disturbed individuals and dysfunctional families, and a predictor of human violence" (p. 521).…”
Section: Human and Animal Violencementioning
confidence: 98%
“…This definition is widely accepted by a large number of disciplines (Becker & French, 2004). In the context of domestic violence, control, coercion, intimidation, and retaliation are some forms of the tactics perpetrators use to torment victims and maintain control (Ascione, Weber, & Wood, 1997;Gallagher, Allen, & Jones, 2008). Abusing animals is another effective tactic used by perpetrators to instill fear, prevent victims from leaving, manipulate children within the home, and provide a preliminary precursor to suggest the violence the perpetrator intends to inflict on the victim(s) (Gallagher et al, 2008).…”
Section: Human and Animal Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Crawford y Bohac 27 reportan que el 59% de mujeres entrevistadas mencionaron que permanecieron más tiempo en el hogar debido al miedo de que las amenazas de daño a la mascota se concretaran. Alrededor de un 70% de mujeres maltratadas han reportado que sus parejas han amenazado, dañado o matado a sus animales para humillarlas y controlar su comportamiento 28 . Los hallazgos de Simmons y Lehmann 29 señalan que los hombres que abusaron de sus animales de compañía demostraron comportamientos más controladores en comparación con aquellos que no lo hicieron.…”
Section: Violencia Psicológicaunclassified
“…59 ASCIONE, F. R., Battered Women's Reports of Their Partners' and Their Children's Cruelty to Animals. Journal of Emotional Abuse, 1/1 (1998) 119-133. doi:10.1300/j135v01n01_06 replicar los actos de violencia 60 . La exposición a estos actos de violencia hacia los animales también tiene repercusiones sobre el desarrollo psicológico del niño 61 .…”
Section: Conclusiónunclassified